Analisis Pertimbangan Hukum Hakim dalam Mengabulkan Perceraian Akibat Pisah Rumah dan Pisah Ranjang di Bawah 6 Bulan Dalam Tinjauan Sema No. 3 Tahun 2023 (Studi Putusan NO. 5960/Pdt.G/2023/Pa/Bdg) - Nurul Mazidah; Ali Khosim; Harry Yuniardi (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2026)
Divorce due to persistent disputes and quarrels is one of the dominant cases examined by the Religious Courts, so guidelines are needed that can guarantee uniformity in the application of the law and avoid disparities in decisions in similar cases. This is the background to the formation of SEMA Number 3 of 2023 as an amendment to SEMA Number 1 of 2022 which stipulates guidelines regarding the provisions of a minimum separation period of six months as a condition for divorce, unless there is an element of domestic violence (KDRT). This study uses a qualitative method with a normative juridical approach that aims to analyze the position of SEMA in the Indonesian legal system as well as the legal considerations and judge's decision in Decision Number 5960/Pdt.G/2023/PA.Bdg which applies a different approach from the guidelines formulated in SEMA Number 3 of 2023. The results of the study indicate that persistent disputes and quarrels are one of the reasons for divorce as regulated in Article 116 of the Compilation of Islamic Law. The SEMA is not included in the hierarchy of laws and regulations, but has a position as a policy regulation (beleidsregel) that serves to provide guidelines for judges in deciding cases. In the a quo case, the judge granted the divorce suit even though the parties had not separated for six months as the indicators formulated in SEMA Number 3 of 2023. The decision was based on trial facts that showed continuous disputes and quarrels and no hope of living together again. This study concludes that the judge's legal considerations remain based on positive legal provisions regarding the grounds for divorce, with an emphasis on realizing benefits and welfare for the parties rather than fulfilling the formal indicators stipulated in the SEMA.